Survival after violence: The post-separation journey of women who have experienced intimate partner violence - Parkin, Sarah Jayne (2017)
Intimate Partner Violence (IPV) is a complex social issue that remains highly prevalent in communities across the world. The impact of IPV includes short-term and long-term psychological, physical, financial and social consequences for women who experience it as well at their immediate and extended families, networks and communities. As research has continued to evolve there has been a move towards exploring the interaction of systemic factors that influence the occurrence of IPV and consequences of IPV long-term. Although researchers have identified that the long-term outcomes for women after leaving an IPV relationship can vary, it appears more research is required in order to understand how women’s post-separation experiences may influence their long-term wellbeing. In particular, it is not yet clear how women conceptualise their post-separation journeys or how such journeys are facilitated by support networks and services. This research project aimed to generate a theory that explains the post-separation journey of women from the perspective of both women who have experienced IPV and individuals who work in the area. In addition this research project aimed to identify which components of the post-separation journey contribute to positive long-term wellbeing for women as well as explore how formal support workers and external factors influence women’s post-separation experiences. In order to achieve these aims a qualitative grounded theory design using semistructured interviews was utilised. Grounded theory was considered the most appropriate approach for the current research as it involves concurrent data collection and analysis procedures that allow theory to emerge from participant’s experiences. The participant sample consisted of 40 individuals: 17 women who have experienced IPV, 15 formal support workers, and 8 women with both personal and professional experiences of IPV. Based on the data a model emerged that identified four main components of a woman’s journey after leaving an IPV relationship: grounding, rebuilding, reflecting, and developing. Each component consists of individual processes identified by both women and formal support workers as key in contributing to a woman’s acceptance of her experiences and sense of wellbeing post-separation. The results indicated that individual post-separation journeys were influenced by women’s interactions with other people, situations, services, communities and the cultural context. Therefore, the model of the post-separation journey of women was positioned within the context of an ecological perspective in order to explain the external processes that participants identified as influencing women’s post-separation journeys. The model assists to enhance what is currently understood about women’s post-separation experiences with important implications for policy, practice, and future researc